All Keynesians now? Public support for countercyclical government borrowing. Issue 1 (30th January 2021) - Barnes, Lucy; Hicks, Timothy
Abstract: In the wake of the 2008 financial crisis, macroeconomic policy returned to the political agenda, and the influence of Keynesian ideas about fiscal stimulus rose (and then fell) in expert circles. Much less is known, however, about whether and when Keynesian prescriptions for countercyclical spending have any support among the general public. We use a survey experiment, fielded twice, to recover the extent to which UK respondents hold such countercyclical attitudes. Our results indicate that public opinion was countercyclical—Keynesian—in 2016. We then use Eurobarometer data to estimate the same basic parameter for the population for the period 2010–2017. The observational results validate our experimental findings for the later period, but also provide evidence that the UK population held procyclical views at the start of the period. Thus, there appear to be important dynamics in public opinion on a key macroeconomic policy issue.